O trabalho doméstico remunerado e feminino: rupturas e continuidades - Matsumoto, Dária Sirqueira (2017)
The purpose of this dissertation is the paid domestic work historically exercised by women from the subalternized layers of the working class, in view of the changes that have occurred, especially those in the process of regulating their social and labor rights, from 2013 to 2016. We sought to analyze the transformations in the area of domestic work, within the historical framework of deep transformations in the world of work, especially for the working class. The central analysis of this study sought to contemplate reflections about work as the first foundation in the process of humanization of the social being and in what way it is materialized in the capital society. In this context, it was intended to analyze the process that led to the formulation of Complementary Law n. 150 of June 2015, and how it has been effective in the daily work of domestic workers in the city of São Paulo. In order to deepen the object of this dissertation, a bibliographical and documentary research was carried out aiming at the historical recovery of the role played by the domestic workers, from Brazil Colônia until the end of the decade 1980 and the paths taken by these workers in the process of political organization in the struggle for the assimilation of labor rights since the provisional government of Getúlio Vargas. For the primary data collection, a qualitative research was carried out, through interviews, using a semi-structured script, with union leaders and domestic workers present in the physical space of the Union of Domestic Workers of the Municipality of São Paulo. It was concluded that domestic work safeguards significant elements from its historical slavers, and through multiple mechanisms of subalternization and exploitation of the female labor force contributes to the process of social reproduction of the middle and bourgeois classes in contemporary capitalist society. However, if the equalization of social and labor rights of domestic workers with other workers represented a significant achievement of historically neglected rights, their preservation and expansion require the strengthening of collective organization and the struggles of domestic workers in alliance with the working class as a whole